Molecular insights into salt stress response in perennial ryegrass (Lolium perenne L.): gene expression and growth performance assessment - Yıldırım, Gözde Hafize; Mesci, Seda; Şengür, Şeyma; Altaf, Muhammad Tanveer (Frontiers in Plant Science, 2026)
Perennial ryegrass (Lolium perenne L.) is a key perennial species with significant agricultural and ecological importance. Salt stress adversely affects plant growth by inducing oxidative stress, reducing biomass accumulation, and impairing physiological functions. In this study, calcium chloride, magnesium chloride, magnesium sulfate, and sodium sulfate treatments were applied to evaluate their effects on salinity-induced molecular and physiological responses. The effects of these treatments on the expression of salt stress–responsive genes Ascobate Peroxidase (APX), Glutathione Reductase (GR), Heavy Metal ATPase (HMA), and Phytochelatin Synthase (PCS) were analyzed using quantitative real-time PCR (qRT-PCR). In addition, agronomic traits including seedling length, fresh and dry weight, plant water content, and dry matter ratio were evaluated. Higher salinity increased stress-related gene expression, but this was not enough to maintain growth or water retention. In contrast, mild to moderate salt stress resulted in more balanced gene expression, reduced physiological damage, and improved plant development. These findings provide insights into the molecular and physiological responses of perennial ryegrass to different salt sources and may support future research on improving salinity tolerance in forage species.